Low-Voltage Solution-Processed Zinc-Doped CuI Thin Film Transistors with NOR Logic and Artificial Synaptic Function - Xiaomin Gan; Wei Dou; Wei Hou; Xing Yuan; Liuhui Lei; Yulan Zhou; Jia Yang; Diandian Chen; Weichang Zhou; Dongsheng Tang (Nanomaterials, 2023)
Low-voltage Zn-doped CuI thin film transistors (TFTs) gated by chitosan dielectric were fabricated at a low temperature. The Zn-doped CuI TFT exhibited a more superior on/off current ratio than CuI TFT due to the substitution or supplementation of copper vacancies by Zn ions. The Zn-doped CuI films were characterized by scanning electron microscope, X-ray diffraction, and X-ray photoelectron spectroscopy. The Zn-doped CuI TFTs exhibited an on/off current ratio of 1.58 × 104, a subthreshold swing of 70 mV/decade, and a field effect mobility of 0.40 cm2V−1s−1, demonstrating good operational stability. Due to the electric-double-layer (EDL) effect and high specific capacitance (17.3 μF/cm2) of chitosan gate dielectric, Zn-doped CuI TFT operates at a voltage below −2 V. The threshold voltage is −0.2 V. In particular, we have prepared Zn-doped CuI TFTs with two in-plane gates and NOR logic operation is implemented on such TFTs. In addition, using the ion relaxation effect and EDL effect of chitosan film, a simple pain neuron simulation is realized on such a p-type TFTs for the first time through the bottom gate to regulate the carrier transport of the channel. This p-type device has promising applications in low-cost electronic devices, complementary electronic circuit, and biosensors.